2016
DOI: 10.1007/s12311-016-0833-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Spinocerebellar Ataxia Type 31: a 4-Year Prospective Study

Abstract: Spinocerebellar ataxia type 31 (SCA31) is known as a late-onset, relatively pure cerebellar form of ataxia, but a longitudinal prospective study on the natural history of SCA31 has not been done yet. In this prospective cohort study, we enrolled 44 patients (mean ± standard deviation 73.6 ± 8.5 years) with genetically confirmed SCA31 from 10 ataxia referral centers in the Nagano area, Japan. Patients were evaluated every year for 4 years using the Scale for the Assessment and Rating of Ataxia (SARA) and the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
19
2
Order By: Relevance
“…Identification of SCA31 repeat clarified clinical picture of SCA31. Typical clinical features can be found in some case reports and cohort studies [10][11][12]. Sakakibara and her colleagues [10] studied 6 SCA31 patients.…”
Section: Pentanucleotide Tggaa Repeat Is Tightly Associated With Spinmentioning
confidence: 98%
See 1 more Smart Citation
“…Identification of SCA31 repeat clarified clinical picture of SCA31. Typical clinical features can be found in some case reports and cohort studies [10][11][12]. Sakakibara and her colleagues [10] studied 6 SCA31 patients.…”
Section: Pentanucleotide Tggaa Repeat Is Tightly Associated With Spinmentioning
confidence: 98%
“…Magnetic resonance imaging of his brain revealed cerebellar atrophy most pronounced in the upper vermis, which is typical for SCA31. Nakamura and his colleagues collected 44 patients with SCA31 and underwent a 4-year prospective study [12]. They evaluated patients yearly using the Scale for the Assessment and Rating of Ataxia (SARA) and the Barthel Index (BI).…”
Section: Pentanucleotide Tggaa Repeat Is Tightly Associated With Spinmentioning
confidence: 99%
“…SCA 31 is a relatively pure cerebellar ataxia with a mean onset at approximately 60 years of age and compatible with a normal life span (100). Originally described in Japan, where it is the third most common form of SCA, SCA31 has since been discovered in other ethnic populations (64,119).…”
Section: Introductionmentioning
confidence: 99%
“…However, progression of SCD is generally slow. It has been reported that the annual changes in SARA total score are 0.80–1.33 for SCA6 and 0.8 for SCA31 2 22 23. Considering the sensitivity of SARA and slow progression, limited change in SARA total score was expected during the observation period selected for our study.…”
Section: Discussionmentioning
confidence: 94%
“…Although the number of repeats can influence the clinical severity of SCA6 and SCA31, data on the number of repeats were not obtained. However, as the effect of the number of repeats on the pathological condition is often subtle in these diseases, this lack of data was considered to be inconsequential 2 23 28. As genetic analyses were not essentially required for CCA diagnosis, it is possible that patients with SCA6, SCA31 or other genetic disorders were included in these studies.…”
Section: Discussionmentioning
confidence: 99%